Groundwater potential identification using frequency ratio method in Kedah - Syed Zabidi, Syarifah Raihana; Bohari, Sharifah Norashikin; Haron Narashid, Rohayu; Saian, Rizauddin; Hashim, Suhaila (Faculty of Civil Engineering, 2025)
Water demand has been rising globally due to various factors such as lack of clean water, climate change, weather conditions, and water pollution. This increasing demand for water is deeply concerning as it has become a basic need for humans, animals, and plants. Therefore, an alternative solution such as groundwater can become one of the sources to support the current needs of water supply as well as to prevent water shortages from occurring. This study aims to identify the groundwater potential area in Kedah by using the Frequency Ratio (FR) method. 12 groundwater conditioning parameters has been divided into three factors which are topographical (elevation, slope, aspect, topographical wetness index (TWI), plan curvature and geomorphology), hydro-geological (drainage density, lithology, aquifers and distance to faults) and other factors (rainfall and landuse) which are obtained through various resources, departments and also agencies. The FR method determines the relationship between dependent variables (tubewell points) and independent variables (groundwater parameters). A total of 354 tubewell points were divided into 70% (248 points) and 30% (106 points) for the training and testing datasets. Subsequently, the identified groundwater potential area was classified into five different classes, which are very high, high, medium, low, and very low. The result shows the highest groundwater area using FR was 23.99% and the lowest groundwater area was 17.09% which is located in the western and the northeast part of Kedah, respectively. The validation using Area Under Curve (AUC) shows a success rate (85.5%) and prediction rate (82.8%), which indicates a good and reliable model. The findings of this study can provide a significant reference for any related agencies and authorities in developing more effective and sustainable groundwater management strategies.